Takhrij Hadis dalam Tafsir Al-Qur’an: Metodologi dan Aplikasinya dalam Pemahaman Kontemporer: Takhrij Hadith in the Tafsir of the Qur'an: Methodology and Its Application in Contemporary Understanding - Anisah Fitri Melenia; Amirul Haq Maqdum Wildany; Nurdiyanto Nurdiyanto (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Hadith serves as an essential source in understanding and explaining the texts of the Qur’an. This study aims to analyze the application of the takhrij hadith methodology in Qur’anic exegesis, examine the influence of hadith validity on the authority of interpretation, and evaluate its relevance in addressing contemporary issues along with its opportunities and challenges. This research employed a qualitative approach using a library research method. The data sources consisted of primary sources, including national and international journal articles and e-books, and secondary sources, such as proceedings and other supporting literature. Data collection techniques involved data gathering, classification, and verification, while data analysis was conducted using inductive content analysis. The findings indicate that the takhrij hadith methodology plays a crucial role in ensuring the validity of hadith used in Qur’anic interpretation. The validity of hadith significantly influences the authority of interpretation, while the application of takhrij results enables Qur’anic exegesis to remain relevant in addressing contemporary issues. Therefore, the takhrij hadith methodology maintains a strategic role in preserving the authenticity and relevance of Qur’anic interpretation in the modern era.